Growth and Characterization of L-Glycine Formate Single Crystal - Sivanesan, T.; Natarajan, V.; Pandi, S. (Asian Journal of Chemistry, 2010)
Single crystal of L-glycine formate is a nonlinear optical crystal. It was grown from aqueous solution by slow evaporation method. The unit cell parameters of the grown crystal were estimated by single crystal X-ray diffraction analysis. The presence of functional groups was identified from FTIR spectrum. Thermal analysis was performed to study the thermal stability of the grown crystal. The UV transmission spectra of this crystal show that the lower cut off wavelength lies at 300 nm.